Clinical adoptive regulatory T Cell therapy: State of the art, challenges, and prospective - Amini, Leila; Kaeda, Jaspal; Fritsche, Enrico; Roemhild, Andy; Kaiser, Daniel; Reinke, Petra (Frontiers in Cell and Developmental Biology, 2023)
Rejection of solid organ transplant and graft versus host disease (GvHD) continue to be challenging in post transplantation management. The introduction of calcineurin inhibitors dramatically improved recipients’ short-term prognosis. However, long-term clinical outlook remains poor, moreover, the lifelong dependency on these toxic drugs leads to chronic deterioration of graft function, in particular the renal function, infections and de-novo malignancies. These observations led investigators to identify alternative therapeutic options to promote long-term graft survival, which could be used concomitantly, but preferably, replace pharmacologic immunosuppression (IS) as standard of care (SOC). Adoptive T cell (ATC) therapy has evolved as one of the most promising approaches in regenerative medicine in the recent years. A range of cell types with disparate immunoregulatory and regenerative properties are actively being investigated as potential therapeutic agents for specific transplant rejection, autoimmunity or injury-related indications. A significant body of data from preclinical models pointed to efficacy of cellular therapies. Significantly, early clinical trial observations have confirmed safety and tolerability, and yielded promising data in support of efficacy of the cellular therapeutics. The first class of these therapeutic agents commonly referred to as advanced therapy medicinal products (ATMPs) have been approved and are now available for clinical use. Specifically, clinical trials have supported the utility of CD4+CD25+FOXP3+ regulatory T cells (Tregs) to minimize unwanted or overshooting immune responses and even the level of pharmacological immunosuppression in transplant recipients. Tregs are recognized as the principal orchestrators of maintaining peripheral tolerance, thereby blocking excessive immune responses and prevent autoimmunity. Here, we summarize rationale for the adoptive Treg therapy, challenges in manufacturing and clinical experiences with this novel living drug and outline future perspectives of its use in transplantation.